A Lexicon Of Basic Vocabulary In The Holy Quran: The “Hamza” Character As A Model/ معجم المفردات الأساسية في القرآن الكريم: حرف الهمزة أنموذجا - Mujahid Mustafa Bahjat; El Sayed Mohamed Salem; Afaf Abdul Ghafoor Hameed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The significance of this research is in gathering this vocabulary and its many derived terms to comprehend and assimilate the main Arabic literatur. It also entails defining their meanings to aid understanding and contemplation.Through the eras, these dictionaries about the Qur'an and its terms gradually appeared with various titles and types, and some gained fame in both the past and the present. Writing and research in this area are still ongoing today. This study is a part of a series that alphabetically arranges the most frequently mentioned words in the Qur'an, which we used to refer to as